2011
DOI: 10.1111/j.1476-5381.2010.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine‐1‐phosphate antibodies as potential agents in the treatment of cancer and age‐related macular degeneration

Abstract: Sphingosine-1-phosphate (S1P) is a pleiotropic bioactive lipid thought to be dysregulated in a variety of disease conditions. In this review, we discuss the roles of S1P in cancer and in wet age-related macular degeneration. We also explore potential treatment strategies for these disorders, including the utility of anti-S1P antibodies acting as molecular sponges to neutralize dysregulated S1P in relevant tissues. AbbreviationsAMD, age-related macular degeneration; CNV, choroidal neovascularization; GLP, good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
70
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 124 publications
(167 reference statements)
4
70
1
Order By: Relevance
“…In addition to FTY720, a promising drug to target this pathway, is an antibody against S1P ligand, which has been shown to effectively inhibit primary tumor growth in various mouse models and has recently entered clinical trials for other indications. 35,40 Another possibility is the use of a novel in vivo siRNA delivery technology, CpG oligonucelotide-conjugated siRNA, to specifically target Toll-like receptor 9-positive cells. 41,42 Toll-like receptor 9-positive cells include normal macrophages and B cells and various types of malignant myeloid and B cells, including ABC-DLBCL.…”
mentioning
confidence: 99%
“…In addition to FTY720, a promising drug to target this pathway, is an antibody against S1P ligand, which has been shown to effectively inhibit primary tumor growth in various mouse models and has recently entered clinical trials for other indications. 35,40 Another possibility is the use of a novel in vivo siRNA delivery technology, CpG oligonucelotide-conjugated siRNA, to specifically target Toll-like receptor 9-positive cells. 41,42 Toll-like receptor 9-positive cells include normal macrophages and B cells and various types of malignant myeloid and B cells, including ABC-DLBCL.…”
mentioning
confidence: 99%
“…It has high affinity and specificity for S1P and blocks S1P-mediated release of the proangiogenic factors IL-8, IL-6, and VEGF from tumor cells in vitro and in vivo, out-competing S1P receptors in binding to S1P [60,[73][74][75]. Sonepcizumab (or it murine counterpart Sphingomab) has demonstrated antipermeability (reduced vascular leakage) and antiangiogenic activity after IVT administration in murine CNV models [67,68,74] and antiangiogenic activity in several mouse and human cancer models, where it retarded the progression of several orthotopic and SC human tumors implanted in nude mice [60].…”
Section: Anti-s1pmentioning
confidence: 99%
“…It has shown better efficacy than bevacizumab, tyrosine kinase inhibitors, and paclitaxel in mouse models of renal cell carcinoma (RCC), and ovarian and lung cancer, respectively (www.LPath.com). Regarding safety, 4 weeks after intraocular injection of up to 1.8 mg of sonepcizumab in non-human primate (NHPs), electroretinograms and fluorescein angiograms were normal, and light microscopy of ocular sections showed no evidence of structural damage [75]. Safety was further supported by toxicology studies in NHPs and mice (with Shingomab) with no adverse events observed at high-dose levels and only a slight decrease in blood lymphocytes at 100 mg kg −1 , expected because of the role of S1P in controlling lymphocyte trafficking [75].…”
Section: Anti-s1pmentioning
confidence: 99%
See 1 more Smart Citation
“…While intracellular targets such as histone deacetylases 1 and 2 (7) as well as TRAF2 (8) have been described, most of the described effects of S1P on cellular processes have been associated with the extracellular functions of S1P mediated through signaling events employing the S1P GPCRs. Thus, one potential therapeutic intervention point is to target the bioactive lipid directly so that it no longer acts as a ligand for its cognate GPCRs or other sites of action (9,10). One way that has been employed to block S1P actions involves the generation of monoclonal antibodies (mAbs) that could act as a molecular sponges to neutralize the bioactive lipid and prevent ligand-receptor signaling (11,12).…”
mentioning
confidence: 99%